2017
DOI: 10.1002/int.21939
|View full text |Cite
|
Sign up to set email alerts
|

Intuitionistic Fuzzy Power Aggregation Operator Based on Entropy and Its Application in Decision Making

Abstract: Atanassov's intuitionistic fuzzy set (IFS) is a generalization of a fuzzy set that can express and process uncertainty much better. There are various averaging operators defined for IFSs. In this paper, a new type of operator called an intuitionistic fuzzy entropy weighted power average ggregation operator is proposed. The entropy among IFSs is taken into consideration to determine the weights. What's more, the similarity is considered to measure the support degree between two elements of the IFS. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 60 publications
1
68
0
Order By: Relevance
“…Fuzzy logic was developed by Zadeh and Mamdani and Assilian, based on which the concept of approximate reasoning was introduced and showed that vague logical statements enable the formation of algorithms that can use vague data to derive vague inferences. Many theories have been promoted by this method, such as Dempster‐Shafer theory, Z‐numbers, and fuzzy reasoning . The definition of fuzzy sets is given as follows:…”
Section: Fuzzy Sets and Ivfssmentioning
confidence: 99%
“…Fuzzy logic was developed by Zadeh and Mamdani and Assilian, based on which the concept of approximate reasoning was introduced and showed that vague logical statements enable the formation of algorithms that can use vague data to derive vague inferences. Many theories have been promoted by this method, such as Dempster‐Shafer theory, Z‐numbers, and fuzzy reasoning . The definition of fuzzy sets is given as follows:…”
Section: Fuzzy Sets and Ivfssmentioning
confidence: 99%
“… Alternative decision entropyEntropy is a measure of uncertainty. It uses the characteristics of information entropy to measure consistency among decision makers, such as weight adjustment algorithm based on entropy theory (Xia & Xu, ) and aggregator optimization (Jiang, Wei, Liu, Li, & Zheng, ). We propose a kind of alternative decision entropy ( E i ) index for individual alternative evaluation value to measure the consistency of group decision‐making alternatives, which is shown as follows.…”
Section: Decision‐making Processmentioning
confidence: 99%
“…Information fusion is to detect, combine, correlate, estimate, and combine multisource data to achieve accurate state estimation and identity estimation. Information fusion technology is widely used in reliability analysis, image processing, intelligent transportation systems, and so on. The advantages of information fusion can be summarized as follows: The information fusion system fuses the information from different sources and overcomes the one‐sidedness of the single information source.…”
Section: Introductionmentioning
confidence: 99%